Senegal Capacity Development Priorities for Climate Services - Braun, Melody; Trzaska, Sylwia; Hansen, James; Grossi, Amanda; Konte, Oumar; Ndiaye, Diabel (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project works to make climate information services and climate-smart agriculture more accessible to millions of smallholder farmers in Senegal and five other target countries). The AICCRA strategy to achieve this goal includes building the capacity of next users to use climate services and support implementation of climate-smart agriculture. Although Senegal has a strong foundation for climate services, the benefits that farming and agropastoral populations obtain from climate services could potentially be limited by insufficient capacity to understand, communicate and apply climate information within these populations and at critical points within the agricultural system, for example, the network of organizations (ANCAR, NGOs, producer organizations) that provide extension and advisory services, local GTPs, university agriculture programs, and rural communities themselves. AICCRA-Senegal held a workshop in Dakar on 9 May 2022 to inform its capacity development strategy. The workshop convened a set of stakeholders representing government, academia and NGOs to identify priority capacity gaps, and opportunities for training and curriculum to address these gaps.